The friendship of Matthew and Paul: A response to a recent trend in the interpretation of Matthew"s Gospel - Willitts, Joel (HTS teologiese studies, 2009)
David Sim has argued that Matthew’s so-called Great Commission (Mt 28:16–20) represents a direct anti-Pauline polemic. While this thesis may be theoretically possible and perhaps fi ts within the perspective of an earlier era in New Testament research, namely that of the Tübingen School, the evidence in both Matthew and the Pauline corpus does not support such a reading of early Christianity. In this paper, I argue that an antithetical relationship between Matthew’s Great Commission and Paul’s Gentile mission as reflected in his epistles is possible only (1) with a certain reading of Matthew and (2) with a caricature of Paul. In light of the most recent research on both Matthew’s Great Commission and the historical Paul, these two traditions can be seen as harmonious and not antithetical in spite of the recent arguments to the contrary. My argument provides a further corrective to the view of early Christianity, which posits a deep schism between so-called Jewish Christianity and Paul’s ostensibly Law-free mission to the Gentiles.